Debreceni bölcsészhallgatónő egy nemzetközi diákkonferencián 1925-ben - Vincze, Tamás (Gerundium, 2017)
An Arts Student from Debrecen at the International Conference in 1925. A conference was held by the World Student Christian Federation in Herkulesfürdő (Băile Herculane, Romania) in 1925. The University of Debrecen was represented by Margit Kis, an arts student in her second year. The conference was an exhilarating experience to the young and enthusiastic lady; she even held a presentation about it to the Debrecen club of the Magyar Evangéliumi Keresztyén Diákszövetség (a Hungarian Christian Student Organization). It was the script of her presentation that she, as a retired teacher, inserted into her memoir a few decades later. We have selected the script of her presentation from her still-unpublished memoir to issue it in the columns of Gerundium. It provides us with valuable information about the main themes of the conference; it is the renewal of the methods of Evangelization the author tells us about the most.